(untitled) (Sport Science Research, 2026)
At present, the development of combat sports is accompanied by increasing demands on the level of athletes’ preparedness and the growing complexity of competitive activity. In karate, performance outcomes are determined not only by the quality of technical execution but also by the level of development of physical and coordination abilities of the athlete. This is especially evident in the kata discipline, where precision, rhythm, and expressiveness of technical actions are of great importance. In this regard, the importance of the rational organization of the training process aimed at comprehensive athlete development is increasing. Analysis of scientific literature shows that karate training requires the integrated development of physical qualities, technical skills, and coordination abilities. The purpose of this study is to analyze scientific and methodological literature devoted to the training of karate athletes (kata discipline), as well as to identify insufficiently studied aspects of the training process. The study employed methods of analysis, generalization, and systematization of scientific literature on issues of physical, technical, and coordination training of karate athletes. The conducted analysis revealed that most studies examine individual aspects of athlete preparation, such as the development of coordination abilities, speed-strength qualities, and technical improvement. At the same time, the issues of comprehensive interaction between different components of training in the kata discipline remain insufficiently studied. In addition, the scientific literature presents differing viewpoints regarding the leading factors influencing athletes’ performance. The obtained data indicate the need for further research aimed at developing more effective training methods for athletes specializing in the kata discipline.